Implementation of P5 to Enhance Creativity and Diversity: The Theme of Local Wisdom through Archipelago Dance Training for Students of SMKN 9 Wajo - Nur Syafutri Hidayat; Marsyanda Marsyanda; Nurmayanti Nurmayanti; Yusrianti Yusrianti; Sam Hermansyah (Universitas Muhammadiyah Enrekang, 2024)
In this era of globalization, there needs to be a balance between education and appreciation of local wisdom with the ability to adapt in an increasingly integrated world. One way that can be done is through culture-based projects, such as traditional Nusantara dance training. The implementation of the Project for Personal and Social Responsibility (P5) with the theme of Local Wisdom through Nusantara Dance Training at SMKN 9 Wajo, aims to increase student creativity while introducing them to cultural diversity. This project integrates traditional dance learning with the development of student creativity within a broader cultural framework. This project shows an increase in student appreciation of local culture as well as a better understanding of cultural diversity at the global level. Data were collected through observation and interviews, then analyzed descriptively. This study used a quantitative approach with an experimental design to assess the impact of Nusantara dance training in the Project for Personal and Social Responsibility (P5) on the creativity and understanding of diversity of SMKN 9 Wajo students. The results showed a significant increase in student motivation mastery, highlighting the effectiveness of game-based learning in creating a fun and interactive learning atmosphere.